Correlation Between Independent Learning Strategies, Competency Appraisal Review as Predictors of Performance in the Nursing Licensure Examination - Cajayon, Sharon (International Journal of Sustainability and Advanced Integrated Research, 2026)
This study examined the effect of independent learning strategies and Competency Appraisal Review (CAR) on nursing graduates' performance in the Philippine Nursing Licensure Examination (PNLE). Anchored on Patricia Benner's From Novice to Expert Theory, the study utilized a quantitative, non-experimental correlational research design to determine the relationships among independent learning strategies, competency appraisal review, and licensure examination performance. The respondents consisted of 150 nursing graduates from a higher education institution in Valenzuela City who took the PNLE between 2022 and 2024 and prepared through self-review. Data were collected using an adapted independent learning strategies questionnaire, the Student Perception Appraisal-Revised-2 (SPA-R2), and a researcher-developed Competency Appraisal Review questionnaire. Descriptive statistics and Pearson correlation coefficient were used for data analysis. The findings revealed that respondents demonstrated favorable independent learning strategies, positive perceptions of academic performance and self-efficacy, and a high perceived impact of Competency Appraisal Review. No significant relationship was found between demographic characteristics and independent learning strategies. However, independent learning strategies showed a significant positive relationship with Competency Appraisal Review and with PNLE performance. Competency Appraisal Review likewise demonstrated a significant positive relationship with licensure examination performance, indicating that structured review and self-directed learning contribute to examination readiness, confidence, and clinical competence. The study concludes that strengthening independent learning strategies and competency appraisal programs can enhance nursing graduates' preparedness for the PNLE. It recommends that nursing students adopt effective self-directed learning practices early, while higher education institutions continue to strengthen competency appraisal and academic support programs. The study supports Sustainable Development Goal (SDG) 3 (Good Health and Well-Being), SDG 4 (Quality Education), and SDG 8 (Decent Work and Economic Growth) by promoting effective educational strategies that prepare competent nursing professionals for safe practice. The findings contribute to educational, institutional, and public health sustainability by providing evidence that may strengthen nursing education, board examination preparation, and workforce readiness.
Keywords: Competency Appraisal Review; Independent Learning Strategies; Nursing Graduates; Philippine Nursing Licensure Examination; Self-Directed Learning